Innovation challenges of digital transformation: Transitioning legacy to the future - Ololade A. Shonubi (Sustainable Futures, 2025)
Considering rapid technological advancement and global competitive pressures, organisations are seeking alternatives to traditional business models through digital transformation initiatives. Legacy systems were not isolated from this change, where reliance on emerging technologies such as AI has become imperative for organisational survival. A related challenge is ''innovation integration'', which refers to the simultaneous adoption of organisational innovation, process innovation, and product/service innovation during digital transitions. Accordingly, this research examines innovation challenges faced by enterprises transitioning from legacy systems to digital futures by empirically testing relationships between emerging technology integration and multiple innovation types across Asian and African contexts using structural equation modelling with quantitative data from managers across two continents. Emerging technology integration demonstrated significant positive relationships with organisational innovation, process innovation, and product/service innovation across both continents. Regional variations influenced innovation capabilities, with African enterprises showing superior process innovation adaptability despite digital infrastructure limitations. Gender differences significantly impacted product and service innovation perceptions amongst managers. Results contribute to academia by enriching digital transformation and innovation management research in emerging economies. Findings contribute to policy and practice by providing strategic insights to enterprise leaders, policymakers, and technology developers regarding innovation strategy, digital capability development, and resource allocation for organisations navigating complex digital transformation challenges whilst leveraging regional innovation strengths and competitive advantages.